2022
DOI: 10.1186/s12870-021-03415-6
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of key gene networks controlling carotenoid metabolism in Xiangfen 1 banana

Abstract: Background Banana fruits are rich in various high-value metabolites and play a key role in the human diet. Of these components, carotenoids have attracted considerable attention due to their physiological role and human health care functions. However, the accumulation patterns of carotenoids and genome-wide analysis of gene expression during banana fruit development have not been comprehensively evaluated. Results In the present study, an integrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Compared to various berries, herbs, and vegetables, banana presents higher antioxidant potential ascribed to the high contents of the described constituents [ 10 ]. In addition, the study of bananas’ carotenoids content reveal that α-carotene, β-carotene, and β-cryptoxanthin present significant provitamin A activity, while lycopene and luteolin possess important antioxidant capacity [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to various berries, herbs, and vegetables, banana presents higher antioxidant potential ascribed to the high contents of the described constituents [ 10 ]. In addition, the study of bananas’ carotenoids content reveal that α-carotene, β-carotene, and β-cryptoxanthin present significant provitamin A activity, while lycopene and luteolin possess important antioxidant capacity [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids are one of the main pigments for coloration, showing yellow, orange, red, or others in plant tissue; they are important components for photosynthesis and are involved in light harvesting and photoprotection, plant growth, and development [1]. Recent studies have shown that kiwifruit [2,3], kumquat [4], tomato [5][6][7], apple [8], carrot [9], banana [10], and apricot [11] contain major accumulations of carotenoids. Furthermore, anthocyanins mainly accumulate in mulberry [12], Chinese Jujube [13], Chokecherry [14], peach [15], citrus [16], grape [17], persimmon [18], black chokeberry [19], eggplant [20], and onion [21].…”
Section: Introductionmentioning
confidence: 99%